1924’te İlkokullarda Tarih Öğretimi: D'alembert Etkisi Altında Türk Deneyimi - Bahri Ata (Turkish History Education Journal, 2014)
The aim of this article is to discuss the affect of European pedagogical heritage to the early Republican period in Turkey by taking into account the teaching of History from the present to the past times at the 3rd grade and the 5th grade in Elementary School. Also I want to show the political and the pedagogical grounds of the application that put into action just after the proclamation of the Republic in 1923. Starting from very limited resources in this subject, I tried to show how this idea might have come to Turkey, who were the main actors in this application by using the historical method. In this context, three questions are tried to be answered. These are as follows; 1. Who put forward the idea of teaching of History at elementary school from the present to the past and on what grounds? * Doç. Dr. , Gazi Üniversitesi, Gazi Eğitim Fakültesi, Tarih Eğitimi ABD, E-posta: bahriata@gazi.edu.tr2. What was the influence of the history education studies at the Second Constitutional Period to the Early Republican Period in Turkey on this matter. 3. What were the results of the teaching of the History from to present to past at the at the rd grade and the 5th grade in Elementary School in 1924.